The associations of muscle mass with glucose and lipid metabolism are influenced by body fat accumulation in children and adolescents - Gao, Liwang; Cheng, Hong; Yan, Yinkun; Liu, Junting; Shan, Xinying; Wang, Xi; Mi, Jie (Frontiers in Endocrinology, 2022)
Objective: To evaluate the prevalence of hyperglycemia and dyslipidemia among different body composition and investigate the associations of body composition indicators, especially the muscle mass, with glucose and lipids metabolism in children and adolescents. Methods: This nationwide cross-sectional study included 8,905 children and adolescents aged 6 to 18 years. All participants underwent dual-energy x-ray absorptiometry and their blood-concentrated glucose and lipids (including TC, TG, LDL-C and HDL-c) were measured . Mixed model, hierarchical analysis, and piecewise regression were used to study the effect of body composition indicators, especially the muscle mass, on glucose and lipids metabolism. Results: The greatest prevalence of high total cholesterol (TC, 6.9% and 6.9%) and high triglyceride (22.3% and 6.6%) was found in both boys and girls with high muscle mass and high fat mass, and girls with high muscle mass and high fat mass also had the highest prevalence of hyperglycemia (7.1%). After fat stratification, higher muscle mass was associated with lower odds of hyperglycemia (OR = 0.62; 95%CI: 0.46,0.84; P = 0.002) and muscle mass was inversely associated with TC (β = −0.07; 95%CI: -0.12,-0.03; P < 0.001) in boys with normal fat mass, but high muscle mass was not significantly associated with hyperglycemia and TC in high-fat-mass group (P = 0.368 and 0.372). Conclusions: The body composition phenotype of high muscle and high fat mass have the highest prevalence of dysglycemia and dyslipidemia. Higher muscle mass was associated with a lower risk of hyperglycemia and TC levels in individuals only with normal fat mass.